Frase Standar Komunikasi Maritim Dalam Simulasi Komunikasi Berbahasa Inggris Di Atas Kapal - Sri Sartini; Lusina Arbety Junirwani (Majalah Ilmiah Bahari Jogja, 2019)
This article is a result of a research in which it belongs to a type of classroom action research. The research was done with the purpose to know how far Standard Maritime Communication Phrases might affect the ability of communication in English both for the purpose of internal and external communication on board vessel toward Nautical science cadets at Yogyakarta Maritime Academy academic year 2016/2017. This research used Kemmis and Mc.Taggart (1988) research approach where there were three main cycles which were preceded with one pre cycle and one post cycle during the research. Each cycles consisted of three meeting period which included the action of planning, conducting, observing, and reflecting. Those four steps were used to get to know the improvement achieved by the subject of the research regarding the usage of SMCP upon their communication ability on board vessel using English for the purpose of making internal and external communication on board. The result of the research showed that out of the four cycles conducted (pre cycle, cycle I, cycle II, cycle III) and post test known that there were significant improvement on the student’s ability of communication which was proven by score improvement they got in every cycle. Besides, the average score of the class also increased time by time and from one cycle to the next cycles. Hence, it is concluded that the use of SMCP might help cadets of Nautical science to increase their communication ability both in making internal and external communication on board vessel.